2005
DOI: 10.1080/09585190500120574
|View full text |Cite
|
Sign up to set email alerts
|

Managing human assets in an uncertain world: applying real options theory to HRM

Abstract: While many authors have proposed a firm's human resources as an asset that can provide value and competitive advantage, the SHRM field has tended to ignore the fact that assets have associated uncertainties and risks. The real options view provides a theoretical framework for how firms manage uncertainties associated with investments in real assets. We apply this logic to analyze the uncertainties associated with human assets and discuss how firms manage these uncertainties through HR 'options' which are capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 37 publications
3
87
0
3
Order By: Relevance
“…For the period between 1999 and 2015, we found that this method has been applied to many cases and in many different fields, from the evaluation of construction projects (Barton & Lawryshyn, 2011;Ford et al, 2002;Garg & Kumar, 2014;Jiao et al, 2007;Oppenheimer, 2002;Parthasarathy & Madhumathi, 2010;Sewalk & Dai, 2014); investments in R&D (Kumaraswamy, 1996;Ming-Cheng & Yen, 2007), in particular those by pharmaceutical companies (Gunther McGrath and Nerkar, 2004;Hartmann & Assan, 2006); the evaluation of IT (information technology) projects (Benaroch, 2002;Fichman, 2004); insurance portfolio strategies; customer relationship management (Maklan et al, 2005); the management and evaluation of intagible assets (Bhattacharya & Wright, 2005, Faiferlick et al 2004, Park et al, 2013; and the assessment of bonds and derivatives (Driffill et al, 2013;Ericsson & Reneby, 2005;Fabozzi et al, 2012, Pyo, 2008Ren-Raw et al, 2002;Singh, 2014, Tompkins, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…For the period between 1999 and 2015, we found that this method has been applied to many cases and in many different fields, from the evaluation of construction projects (Barton & Lawryshyn, 2011;Ford et al, 2002;Garg & Kumar, 2014;Jiao et al, 2007;Oppenheimer, 2002;Parthasarathy & Madhumathi, 2010;Sewalk & Dai, 2014); investments in R&D (Kumaraswamy, 1996;Ming-Cheng & Yen, 2007), in particular those by pharmaceutical companies (Gunther McGrath and Nerkar, 2004;Hartmann & Assan, 2006); the evaluation of IT (information technology) projects (Benaroch, 2002;Fichman, 2004); insurance portfolio strategies; customer relationship management (Maklan et al, 2005); the management and evaluation of intagible assets (Bhattacharya & Wright, 2005, Faiferlick et al 2004, Park et al, 2013; and the assessment of bonds and derivatives (Driffill et al, 2013;Ericsson & Reneby, 2005;Fabozzi et al, 2012, Pyo, 2008Ren-Raw et al, 2002;Singh, 2014, Tompkins, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…In fact, some of them literally say that it is a 'differential factor' for corporations, this is, a competitive advantage factor (Den Hartog and Verburg, 2004;Bhattacharya and Wright, 2005;Hiltrop, 2006;Clardy, 2008). Thus, 22 companies state the guidelines in the human resources policy explicitly and it must additionally be remembered that 8 firms identify human resources development as one of the key corporate strategies.…”
Section: Human Resources Management Principlesmentioning
confidence: 99%
“…The option to defer or abandon when new information becomes available is attractive, hence the use of temporary employees. Bhattacharya and Wright (2005) suggest that much uncertainty relates to hiring because of the largely irreversible costs associated with recruitment, training and benefits, as well as maintenance of employees, costs regarded by Jacobs (2007) as sunk. …”
Section: Real Optionsmentioning
confidence: 99%